The Influence of Instructional Leadership, Teacher Competence, and the Use of Information Technology on the Effectiveness of Deep Learning at SDN Daerah 3t in Batang Tuaka Subdistrict, Indragiri Hilir, Riau - Dewi Yulianti; Priadi Surya (FKIP - Universitas Riau, 2026)
This study examines the effects of instructional leadership, teacher competence, and information technology utilization on the effectiveness of deep learning in public elementary schools located in the underdeveloped, frontier, and outermost (3T) areas of Batang Tuaka District, Indragiri Hilir Regency, Riau Province, Indonesia. A quantitative ex post facto correlational design was employed involving 101 teachers selected through proportionate cluster random sampling. Data were collected using validated and reliable Likert-scale questionnaires and analyzed using multiple linear regression with IBM SPSS version 31 after meeting the assumptions of normality, multicollinearity, and heteroscedasticity. The findings reveal that instructional leadership has a positive but non-significant effect on deep learning effectiveness (p = 0.391). In contrast, teacher competence (p = 0.007) and information technology utilization (p < 0.001) significantly and positively influence deep learning effectiveness. Simultaneously, the three variables significantly affect deep learning effectiveness (p < 0.001), explaining 49.9% of its variance. These findings suggest that improving teacher competence and optimizing information technology utilization are essential strategies for strengthening deep learning, particularly in schools located in 3T areas. Future research should investigate additional factors influencing deep learning effectiveness to provide a more comprehensive understanding of quality learning improvement in disadvantaged educational contexts.